The Impact of COVID-19 on Music Event Organizers Work Plan in Indonesia: A Case Study of Emvrio Production - Sari Wahyuni; Safira Syahdani Guci Fahmi; Natasha Radinda Putri Taifur; Andrea Kirana Anggraeni; Hanni Hafsari Putri (ASEAN Journal on Hospitality and Tourism, 2022)
This study aims to analyze the impact of the Covid-19 pandemic on changes in the work plan of music event organizers in Indonesia. This case study was conducted on Emvrio Production as we believe that Emvrio, as one of the music event organizers in Indonesia with various successful projects such as their Berdendang Bergoyang Festival, would most likely experience changes in their work plan amidst this Covid-19 pandemic. We conducted the case study by interviewing 6 members of Emvrio Production from various positions within the company.